Scene of the cybercrime - Cross, Michael, 1965-; Shinder, Debra Littlejohn (Burlington, MA : Syngress Pub., 2008)
When it comes to computer crimes, the criminals got a big head start. But the law enforcement and IT security communities are now working diligently to develop the knowledge, skills, and tools to successfully investigate and prosecute Cybercrime cases. When the first edition of "Scene of the Cybercrime" published in 2002, it was one of the first books that educated IT security professionals and law enforcement how to fight Cybercrime. Over the past 5 years a great deal has changed in how computer crimes are perpetrated and subsequently investigated. Also, the IT security and law enforcement communities have dramatically improved their ability to deal with Cybercrime, largely as a result of increased spending and training. According to the 2006 Computer Security Institute's and FBI's joint Cybercrime report: 52% of companies reported unauthorized use of computer systems in the prior 12 months. Each of these incidents is a Cybecrime requiring a certain level of investigation and remediation. And in many cases, an investigation is mandates by federal compliance regulations such as Sarbanes-Oxley, HIPAA, or the Payment Card Industry (PCI) Data Security Standard. Scene of the Cybercrime, Second Edition is a completely revised and updated book which covers all of the technological, legal, and regulatory changes, which have occurred since the first edition. The book is written for dual audience; IT security professionals and members of law enforcement. It gives the technical experts a little peek into the law enforcement world, a highly structured environment where the "letter of the law" is paramount and procedures must be followed closely lest an investigation be contaminated and all the evidence collected rendered useless. It also provides law enforcement officers with an idea of some of the technical aspects of how cyber crimes are committed, and how technology can be used to track down and build a case against the criminals who commit them. Scene of the Cybercrime, Second Editions provides a roadmap that those on both sides of the table can use to navigate the legal and technical landscape to understand, prevent, detect, and successfully prosecute the criminal behavior that is as much a threat to the online community as "traditional" crime is to the neighborhoods in which we live. Also included is an all new chapter on Worldwide Forensics Acts and Laws. * Companion Web site provides custom tools and scripts, which readers can download for conducting digital, forensic investigations. * Special chapters outline how Cybercrime investigations must be reported and investigated by corporate IT staff to meet federal mandates from Sarbanes Oxley, and the Payment Card Industry (PCI) Data Security Standard * Details forensic investigative techniques for the most common operating systems (Windows, Linux and UNIX) as well as cutting edge devices including iPods, Blackberries, and cell phones.
1: Facing the Cybercrime Problem Head-on; 2: Emerging Cybercrime Techniques; 3: Understanding the People on the Scene; 4: The Computer Investigation Process; 5: Acquiring Data, Duplicating Data, and Recovering Deleted Files; 6: Understanding Network Intrusions and Attacks; 7: Understanding Cybercrime Prevention; 8: Implementing Cybercrime Detection Techniques; 9: Collecting and Preserving Digital Evidence; 10: Analyzing Windows Systems. 11: Analyzing Linux Systems. 12: Investigating UNIX Systems. 13: Achieving Compliance with Federal Regulations 14: Building the Cybercrime Case; 15: Worldwide Forensics Acts and Laws.
Previous ed.: published as by Debra Littlejohn Shinder. 2002.
Includes bibliographical references and index.
Keywords: Computer security; Computer networks -- Security measures; Computer crimes -- Investigation; Forensic sciences; Electronic books